2013
DOI: 10.4103/1947-489x.210544
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of dermatophyte culture by clinical features: Saving time and cost in resource-poor settings

Abstract: Background: Tinea capitis is common among children worldwide. Confirmation of diagnosis for early commencement of therapy and control has continued to be a major challenge in resource-poor settings. Patients and Methods: This cross-sectional study recruited 185 children in the rural community of Osogbo, Nigeria. Two thirds of the study population were children aged 5 to 8 years. Clinical history was documented and scalp scrapping of scales and hairs was obtained for microscopy and culture. Two sided fisher exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…This is not very different from the study by Amen and Okolo (2004), which found a strong link between dermatophytosis and domestic animals [21]. A similar study also found that the overwhelming majority of the children who had tinea capitis had unlimited close contact with goats, sheep, and dogs that roam around and are not kept in closed pens [23]. The practice of rearing free-range and stray animals around the home and neighborhoods, which subsequently leads to the easy transmission of zoophilic tinea capitis, is further fostered in the cultural belief that the rearing of animals, especially free-range animals, keeps away evil from their owners [11].…”
Section: Discussionsupporting
confidence: 44%
“…This is not very different from the study by Amen and Okolo (2004), which found a strong link between dermatophytosis and domestic animals [21]. A similar study also found that the overwhelming majority of the children who had tinea capitis had unlimited close contact with goats, sheep, and dogs that roam around and are not kept in closed pens [23]. The practice of rearing free-range and stray animals around the home and neighborhoods, which subsequently leads to the easy transmission of zoophilic tinea capitis, is further fostered in the cultural belief that the rearing of animals, especially free-range animals, keeps away evil from their owners [11].…”
Section: Discussionsupporting
confidence: 44%